Chemical Vapor Deposition Recent Advances and Applications in Optical, Solar Cells and Solid State Devices - Neralla, Sudheer (IntechOpen, 2016)
This book provides an overview of chemical vapor deposition (CVD) methods and recent advances in developing novel materials for application in various fields. CVD has now evolved into the most widely used technique for growth of thin films in electronics industry. Several books on CVD methods have emerged in the past, and thus the scope of this book goes beyond providing fundamentals of the CVD process. Some of the chapters included highlight current limitations in the CVD methods and offer alternatives in developing coatings through overcoming these limitations.